Analisis Kekuatan terhadap Rencana Struktur Penyangga Helideck pada Bangunan Lepas Pantai - Erlina Kusumawati; Muhamad Ari; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
Exploration activities of the oil and gas are done in a long time, and usually this activities is done in deep sea and far from the maindland. To facilitate transportation then used helicopter, therefore the rig must be equipped with a helideck for helicopter landing. Helideck and the support structure are important elements of safety because of its role in emergency evacuation and normal operations. To meet the safety factor, helideck must have strong supporting structure, in accordance with the permitted material. So we need examine about the strength of plan support structure by doing load calculations as well as load simulation by Finite Element Methode when helicopter landing under normal conditions and emergency conditions. From the simulation and analysis results, it is known that the maximum stress applied to the helideck support structure when helicopter landing under normal conditions is 54,88 MPa and under emergency conditions is 65,22 MPa. The maximum deflection occuriing in the helideck support srtructure when helicopter landing under normal conditions is 14,45 mm and under emergency conditions is 17,19 mm. The helideck support structure is safe according to the criteria, since the safety factor simulation results when helicopter landing under normal conditions is 4,9 and under emergency conditions is 4,2 and the maximum deflection value that occurs is bellow the maximum allowable deflection value